SMK Negeri 2 Solok: Dynamics of Curriculum Merdeka, Tefa, and Successful Internships in Education Transformation - Latifah, Ulfi; Saputri, Annisa; Zaus, Anggun Agni; Jalinus, Nizwardi; Waskito, Waskito (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2024)
This study aims to investigate the implementation and impact of the Merdeka curriculum at SMK Negeri 2 Solok, focusing on key stakeholder perspectives, challenges, and successes associated with this innovative educational framework. The study adopts a mixed methods approach, combining in-depth interviews with the deputy principal responsible for overseeing the curriculum, statistical analysis for quantitative data, and thematic analysis for qualitative insights. The findings reveal that the Merdeka Curriculum offers advantages in flexibility and adaptability, despite encountering implementation challenges due to limited resources. Two significant outcomes highlight the necessity for targeted teacher training and the diverse perspectives of students. The results contribute valuable insights for educators, administrators, and policymakers to enhance the effectiveness of their curricula, particularly for professional educational institutions seeking to implement adaptive and student-centered teaching methods. The research underscores the importance of understanding the experiences of deputy principals, providing a unique perspective on the challenges and opportunities presented by the Merdeka Curriculum. Furthermore, the study offers detailed suggestions for resource allocation and career advancement, offering practical implications for educational institutions striving to implement innovative teaching methodologies.